2012
DOI: 10.1186/1746-4269-8-38
|View full text |Cite
|
Sign up to set email alerts
|

Wildlife uses and hunting patterns in rural communities of the Yucatan Peninsula, Mexico

Abstract: BackgroundSubsistence hunting is a traditional practice providing food and many other goods for households in the Yucatan Peninsula, southeast Mexico. Economic, demographic, and cultural change in this region drive wildlife habitat loss and local extinctions. Improving our understanding about current practices of wildlife use may support better management strategies for conserving game species and their habitat. We aimed to evaluate if wildlife use remained relevant for the subsistence of rural residents of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0
37

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(112 citation statements)
references
References 41 publications
1
74
0
37
Order By: Relevance
“…The significant number of mentions of the common deer (M. gouazoubira) may be related to its size (amount of biomass obtained in hunting activity), to the appreciable flavor and tenderness of the meat, or to it being considered "healthy". Santos-Fita et al (2012), in a similar study with rural communities in Mexico, also found Mazama sp. among the animals with most mentions for consumption due to palatability and the nutritional value of its meat.…”
Section: Categories Of Usementioning
confidence: 72%
See 1 more Smart Citation
“…The significant number of mentions of the common deer (M. gouazoubira) may be related to its size (amount of biomass obtained in hunting activity), to the appreciable flavor and tenderness of the meat, or to it being considered "healthy". Santos-Fita et al (2012), in a similar study with rural communities in Mexico, also found Mazama sp. among the animals with most mentions for consumption due to palatability and the nutritional value of its meat.…”
Section: Categories Of Usementioning
confidence: 72%
“…From a conservation point of view, the way people interact with locally important biological resources must be taken into account, since it is dynamic and susceptible to various influences (economic and socio-cultural factors, for example), a fact that is discussed in specialized literature (Alves 2009, Alves & Dias 2010, Santos-Fita et al 2012, Hunt 2013. Thus, understanding the issues arising from this relation (social and ecological elements) may be useful to guide conservation strategies of wildlife resources at local level.…”
Section: Introductionmentioning
confidence: 99%
“…Productive activities include agriculture, livestock farming, beekeeping, and coal extraction; also practiced are subsistence hunting and, to a lesser extent, hunting (Weber 2000;Escamilla et al 2000;Reyna-Hurtado and Tanner 2007;Santos-Fita et al 2012;Briceño-Méndez et al 2014;Briceño-Mendez et al 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have noted that hunters are sometimes prone to underreporting small-mammal catches (Smith 1976;Koster 2007;Santos-Fita et al 2012). Similarly, not every study ran for a full year, and may, therefore, have under-represented species which are only hunted in certain seasons.…”
Section: Assumptionsmentioning
confidence: 99%